Lower dietary folate intake increases the risk of autoimmune thyroiditis - Lijun Chen; Changjian Yan; Yingxuan Lin; Liqun Huang; Chunling Huang; Zhida Wei; Hongli Lin; Xiaohong Wu; Ruhai Lin; Zhengrong Jiang; Huibin Huang (Frontiers in Nutrition)
BackgroundAutoimmune thyroid diseases (AITDs) are a group of organ-specific autoimmune disorders resulting from the loss of immune tolerance, with autoimmune thyroiditis (AIT) being the most common phenotype. In recent years, folate, an essential nutrient, has been associated with the onset of various autoimmune diseases. However, the relationship between dietary folate intake and AIT remains unclear.ObjectiveThis study seeks to explore the possible link between folate consumption and AIT.MethodsThis study is based on the 2009–2010 National Health and Nutrition Examination Survey (NHANES) data to analyze the connection between folate consumption and the risk of AIT. A total of 2037 participants were included in the study. Based on TPOAb or TgAb levels, participants were classified into the AIT group (n = 144) and the non-AIT group (n = 1893), and clinical variables were compared between these two groups. Univariate and multivariate logistic regression models were employed to examine the relationship between AIT risk and various factors, including demographics, complete blood count, blood biochemistry parameters, thyroid function test, urinary iodine concentration, as well as intakes of vitamin B12 and folate. A diagnostic model for AIT was constructed using dietary folate intake, TSH, age, sex, urinary iodine concentration, and vitamin B12 intake.ResultsThe analysis results indicate that the dietary folate intake of AIT patients was significantly lower than that of the non-AIT group (356.7 ± 172.4 vs. 396.1 ± 200.3mcg/day, p < 0.05). Participants in the high dietary folate intake group showed a 52% lower risk of AIT compared to the low-intake group (OR = 0.48, 95%CI: 0.33–0.71, p < 0.001) in the univariate analysis. This association remained significant after multivariable adjustment (OR = 0.53, 95%CI: 0.35–0.80, p = 0.003).ConclusionThis cross-sectional study is the first to explore the association between dietary folate consumption and the likelihood of developing AIT. The results suggest that lower dietary folate intake may be an independent factor contributing to AIT. It may provide new insights for the development of future dietary prevention strategies for AIT.